The Canon EOS Digital Rebel T1i/500D companion - Long, Ben (O'Reilly, 2009)
Through easy-to-follow lessons, this handy book offers a complete class on digital photography, tailored specifically for people who use the Canon EOS Digital Rebel T1i/500D. This is not your typical camera guide: rather than just show you what all the buttons do, it teaches you how to use the Digital Rebel's features to make great photographs -- including professional-looking images of people, landscapes, action shots, close-ups, night shots, HD video, and more. With Ben Long's creative tips and technical advice, you have the perfect, camera-bag-friendly reference that will help you capture stunning pictures anywhere, anytime. The Canon EOS Digital Rebel T1i/500D Companion will show you how to: Take creative control and go beyond automatic settings Learn the basic rules of composition Capture decisive moments, including fast-moving objects Discover ways to use a flash indoors and outdoors Learn about different lenses, and the best time to use them Understand the options for shooting RAW, and whether it's right for you Use the Digital Rebel's ability to shoot high definition video.